A Simplex-Optimized Chromatographic Separation of Phytoconstituents in Cardioprotective Polyherbal Formulation and Crude Drugs - Chauhan, Payal (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The study aims to develop and validate accurate, precise, and robust reverse phase high performance liquid chromatographic method for determination of phytoconstituents such as ascorbic acid, gallic acid, quercetin, and reserpine in polyherbal formulation and crude drugs. Materials and Methods: The adequate chromatographic separation was accomplished on C18 column, 250 × 4.6 mm, 5 μmAgilent eclipse using mobile phase 0.05 M sodium dihydrogen phosphate buffer (pH-4 adjusted with 1% Orthophosphoric acid): Acetonitrile with properly resolved gradient program. The flow rate was 1 ml/min, and the ultraviolet detection was monitored at 227 nm. The retention time of ascorbic acid, gallic acid quercetin and reserpine was found to be 3.44 min, 5.26 min, 10.02 min and 13.24 min, respectively. The method was validated as a final verification of method development concerning precision, linearity, accuracy, sensitivity and robustness as per International Council for Harmonization (ICH) guideline Q2 (R1). Results and Discussion: A method is considered to be linear as the correlation coefficient was found to be within acceptance criteria. The detector response was linear in the range of 50–250 μg/ml Ascorbic acid, 100-300 μg/ml Gallic acid, 100-300 μg/ml, Quercetin and 50–250 μg/ml Reserpine. The % RSD of peak area response due to Ascorbic acid, Quercetin, Reserpine and Gallic acid in five replicate injections of standard solution was to be less than 2.0%, and system suitability parameters were passed. Conclusion: The proposed method was effectively applied for the simultaneous estimation of Ascorbic acid, Gallic acid, Quercetin and Reserpine in Polyherbal formulation and in crude drugs.